Quality of life in patients with diabetes mellitus - Ahmed, Naima; Tomalika, Nehlin; Rhaman, Mir Masudur; Momtaz, Hasina; Haque, Md Mahmudul (IMC Journal of Medical Science, 2019)
Background and objectives: Diabetes mellitus (DM) perpetually affects the quality of life. This non-communicable lifelong disease usually develops micro and macro-vascular complications affecting vital organs. Thus, it reduces the functional capability of health as assessed by the health-related quality of life (HRQOL) measuring tools. It is not known, how much HRQOL of the diabetic population in Bangladesh is affected. Therefore, the objective of the present study was to estimate the levels of HRQOL of cases with DM attending a tertiary care hospital in Dhaka city. The study considered socioeconomic condition, nutritional status, duration of diabetes and treatment modalities while analyzing the HRQOL. Methods: This study was conducted in a tertiary care hospital in Dhaka city from July 2016 to June 2017. Patients with DM were considered eligible and were recruited. Those who were found to have complications like retinopathy, nephropathy, neuropathy, hypertension and stroke were excluded based on previous investigations. Once selected, the study protocol was described to each of the diabetic patients. If agreed, the participant was interviewed. Short Form health survey questionnaire (SF-36) was used for assessment of HRQOL. The assessment of physical health components included physical function, role physical, body pain, and general health. Mental health components were emotion, vitality and social function. Results: A total of 150 diabetic patients (m/f: 80/70) were included in the study. Comparisons of demographic variables between male and female participants showed no significant difference. As regards HRQOL, physical function score was significantly reduced among those who had diabetes for more than 10 years (p=0.049). General health component was significantly impaired among those who had higher BMI (<30kg/m2; p= 0.016) and post-prandial hyperglycemia. Longer duration of DM (>10yrs) and higher BMI significantly reduced components of mental health quality. Conclusion: The study revealed that the overall physical and mental quality of life was significantly affected by longer duration of diabetes, obesity and glycemic status. IMC J Med Sci 2018; 12(2): 73-79